Training military center in the system of university education - Semak V. V. (Priority directions of scienceand education development, 2016)
the article describes the main features of student's education in military training centers at federal state educational institutions of higher education on military training programs.
Keywords: военное образование; military education; военная подготовка; military training centers; military training; учебные военные центры